MODELING OF THE FLIGHT CREW’S TRAINING PROCESSES ON SIMULATORS IN THE INTERESTS OF GUARANTEED Flight SAFETY - I. G. Sokhin (Научный вестник МГТУ ГА, 2016)
The paper covers the problem how to control flight crew training on simulators to ensure the fulfillment requirements for the quality of their activity in training non-standard situations which can happen in flight. It is shown that the existing methodology of training pilots on simulators does not ensure the quality of their activity in those non-standard situations. The paper puts forward an adaptive control method (АМC-method) of the simulator training of flight crews using mathematical modeling the states of their operator competences. The main advantage of the new method is the possibility to obtain statistical quality indicators of flight crew activity in non-standard situations and, thereby, to control the fulfillment of prescribed requirements for safety and reliability of space missions.